2012
DOI: 10.1901/jaba.2012.45-155
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intraverbal Training Procedures for Children With Autism

Abstract: We compared the effectiveness of three training procedures, echoic and tact prompting plus error correction and a cues-pause-point (CPP) procedure, for increasing intraverbals in 2 children with autism. We also measured echoic behavior that may have interfered with appropriate question answering. Results indicated that echoic prompting with error correction was most effective and the CPP procedure was least effective for increasing intraverbals and decreasing echoic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 4 publications
0
30
0
4
Order By: Relevance
“…Other researchers have found that the echoic prompts resulted in faster acquisition of intraverbal behavior for several young children with autism (Ingvarsson and Le 2011;Kodak et al 2012). Ingvarsson and Le (2011) suggested that their participants' extensive exposure to vocal prompts and transfer-of-control procedures likely accounted for the greater efficiency of the echoic condition, a notion supported by the findings of Coon and Miguel (2012) who found that participants' recent history with prompting tactics affected which modality was more efficient.…”
mentioning
confidence: 97%
“…Other researchers have found that the echoic prompts resulted in faster acquisition of intraverbal behavior for several young children with autism (Ingvarsson and Le 2011;Kodak et al 2012). Ingvarsson and Le (2011) suggested that their participants' extensive exposure to vocal prompts and transfer-of-control procedures likely accounted for the greater efficiency of the echoic condition, a notion supported by the findings of Coon and Miguel (2012) who found that participants' recent history with prompting tactics affected which modality was more efficient.…”
mentioning
confidence: 97%
“…A number of recent studies identified effective strategies to teach intraverbal responses to children with ASD (e.g., Ingvarsson and Hollobaugh 2011;Ingvarsson and Le 2011;Kodak et al 2012). Intraverbal training may be conducted within the format of discrete-trial instruction (DTI; Smith 2001) to provide repeated practice opportunities.…”
mentioning
confidence: 99%
“…Following two consecutive sessions with correct prompted responding at or above 90%, the experimenter provided a 2‐s delay following the discriminative stimulus before modeling the correct response. Thereafter, the criterion to increase the prompt delay was one session in which 50% or more of the errors consisted of a no response (omission errors; Kodak, Fuchtman, & Paden, ); the progression of the prompt delays was 2 s, 5 s, 10 s, and 20 s. The criteria for increasing the prompt delay were held constant across conditions such that each condition progressed through the changes in prompt delay independently. This was done to emulate how the PPD would be applied in practice when the conditions are not being compared in a formal evaluation.…”
Section: Methodsmentioning
confidence: 99%